Knowing is Half The Battle: The Effect of Diagnosing Diabetes on Alcohol Consumtion in China - Shen, Yichen (Universitas Airlangga, 2023)
The diagnosis of a disease can significantly change the health behavior of a population, leading to a significant improvement in public health. This study observed how China's alcohol consumption changes in response to a diabetes diagnosis from a health check-up. The 1991–2015 China Health and Nutrition Survey was used in this study. A difference-in-difference with a fixed effect model was applied to the dataset. The survey's 2009 health check-up generated the treatment status, also known as the diabetes diagnosis status. The results showed that the diagnosis of diabetes decreased alcohol consumption (Beta = -0.032; 95% CI = -0.022, -0.011; P-value = 0.015). The effect was more prevalent and significant among men (Beta = -0.077; 95% CI = -0.122, -0.031; P-value = 0.001). The findings of this study showed that a health check-up to inform individuals of their diabetes status could alter alcohol consumption behavior in China. This implies that a health check-up policy in developing countries could lead to significant health improvements and reduce the costs associated with alcohol consumption.